Ethics in an era of globalization (Hampshire, 2008)
This much-needed volume represents all that is new in the field of global ethics. It recognizes the emergence of the search to move beyond relativism and the study of ethical aspects of globalization, acknowledging aspects of globalization that make ethical reasoning itself a challenging task. As such the young field of global ethics is a search for new approaches and methodologies that go beyond existing ones and succeed in addressing these ethical issues of globalization. This volume presents these new developments, focusing specifically on how to re-conceive ethics in order to come to grips with ethical and political life today. It sets out an agenda for the field of global ethics, addresses the critiques and illustrates the rapprochement of global ethics. This is a valuable collection of essays that connect theoretical innovation with substantive issues in the public realm and hence is suitable for a wide audience across philosophy, politics, international relations and development studies.
Keywords: Globalization-Moral and ethical aspects